Antibiotic Susceptibility and Technological Properties of Leuconostoc citreum for Selecting Starter Candidates - Sumin Lee; Sojeong Heo; Gawon Lee; Yura Moon; Minkyeong Kim; Mi-Sun Kwak; Do-Won Jeong (Microorganisms)
Antibiotic susceptibilities, hemolytic activities, and technological properties of 46 Leuconostoc citreum isolates from kimchi were evaluated to select starter candidates. All strains were susceptible to clindamycin and erythromycin, while some exhibited resistance to ampicillin, chloramphenicol, gentamicin, streptomycin, and tetracycline; all were resistant to kanamycin based on the EFSA breakpoint values for Leuconostoc species. PCR analysis did not detect resistance genes for these six antibiotics in any strain. None of the strains demonstrated clear α- or β-hemolytic activity. All strains thrived in a medium supplemented with 6% NaCl, displaying protease activity and acid in media containing 6% and 3% NaCl, respectively. Consequently, five strains, AK5T17, AK5T19, AK10M04, DMLC16, and YK10T20, were identified as starter candidates, with L. citreum strain DMLC16 emerging as the top choice due to its elevated protease and acid production capacities. These findings support the safe application of L. citreum strain DMLC16 as a starter candidate in fermented food production.